Trans-Communication through Character Makeup in Movie “Khun Pan 2” - Kamnon, Krit (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This article aimed to analyze aspects of trans-communication through special effect makeup for character in the movie and post-modern concept influencing signification for meaning through character makeup in the movie “Khun Pan 2”. The study revealed that the aspect through special effect makeup appearing that former media transformed into messages in following media in the correlation between media and message. However, the significance through makeup of character “Khun Pan” and “Khun Jone” in the movie of digital era/ postmodern era required 4 concepts including 1) first dimension, reproduction of meaning of heroes and villains character makeup in the ideal of Thai culture as archetypes 2) second dimension, transtextuality of character makeup among intertextuality, paratextuality and hypertextuality 3) third dimension, nostalgia of the makeup from simulation to simulacrum with society acceptation of the truth to illustrate receivers the past memorable characters and 4) final dimension, discontinuity of hyperreality makeup conveying the dynamic of discontinuing between time and place.